A Recursive Soft-Input Soft-Output Decoding Algorithm - Karakchieva, Liudmila; Trifonov, Peter (IEEE transactions on communications, 2024)
A reduced complexity symbolwise maximum a posteriori probability (MAP) decoding algorithm for linear block codes is presented. This algorithm is based on the recursive trellises and performs two passes over the recursion tree. Probability-domain and Log-Max implementations are considered. Numeric results show that the proposed method has lower complexity compared to other known recursive algorithms and the classical BCJR algorithm. The complexity analysis for random codes is provided.